(untitled) (Advances in Applied Mathematics and Mechanics, 2010)
This paper presents the application of a new method for obtaining new exact solutions of some well-known nonlinear partial differential equations. The Rational Hyperbolic method is used for handling the Zhiber-Shabat equation and the related equations such as Liouville, Sinh-Gordon, Dodd-Bullough-Mikhailov and Tzitzeica-Dodd-Bullough equations. We show power of the Rational Hyperbolic method that is simple and effective for solving nonlinear partial differential equations.